Interface design for high energy density polymer nanocomposites. (4th July 2019) - Luo, Hang; Zhou, Xuefan; Ellingford, Christopher; Zhang, Yan; Chen, Sheng; Zhou, Kechao; Zhang, Dou; Bowen, Chris R.; Wan, Chaoying
Abstract : A detailed overview on interface design and control in polymer based composite dielectrics for energy storage applications. Abstract : This review provides a detailed overview on the latest developments in the design and control of the interface in polymer based composite dielectrics for energy storage applications. The methods employed for interface design in composite systems are described for a variety of filler types and morphologies, along with novel approaches employed to build hierarchical interfaces for multi-scale control of properties. Efforts to achieve a close control of interfacial properties and geometry are then described, which includes the creation of either flexible or rigid polymer interfaces, the use of liquid crystals and developing ceramic and carbon-based interfaces with tailored electrical properties. The impact of the variety of interface structures on composite polarization and energy storage capability are described, along with an overview of existing models to understand the polarization mechanisms and quantitatively assess the potential benefits of different structures for energy storage. The applications and properties of such interface-controlled materials are then explored, along with an overview of existing challenges and practical limitations. Finally, a summary and future perspectives are provided to highlight future directions of research in this growing and important area.